STUDENTS’ PREPARATION FOR SPEECH PERFORMANCE IN GRADE XI STUDENT AT SMAS GKPI PADANG BULAN - Christy Tambunan (Sean Institute, 2022)
This study motivated by the phenomenon in SMAS GKPI Padang Bulan. The teacher reported that the students did not know how to do well on a regular basis, and the teacher also said that the teacher used several methods to improve the students' speaking skills when performing speech, but no significant progress was made. This issues supported by students confession that they have problem when preparing speech and they feel anxiety. To solve this problem, researcher decided to conduct a research toward grade XI social students of SMAS GKPI Padang Bulan. The design of this research is quantitative descriptive with 20 samples of students from grade XI SMAS GKPI Padang Bulan. The result of the study shows that; First, Confidence problem is difficulties which affects students speech in grade XI Social at SMAS GKPI Padang Bulan by the academic year of 2022/2023. Second, Grade XI social students speech preparation is all of them making introduction and closing, but they have lack of skill in formulating it both introduction and closing. Third, Students performance related to internal factor is that they are lacking in making an organized and structured sentence while in eksternal factor they have lack skill in speech due to they never join speech competition. So that teacher need to guide students and students need to improve their speech preparation so it will improve their confidence and performance Keywords : Speech Preparation, Performance, Social Students.